Sejarah Budaya Partai Keadilan Sejahtera di Jepara Tahun 1999-2009 - Ummi Nur Lutfiyah; Alamsyah Alamsyah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
This article discusses about the development of the Prosperous Justice Party in Jepara with various dynamics. The party originally called the Justice Party in Jepara, was founded by former campus religious activists. Initially, this party became a cadre party that applied strict standards in the recruitment process through the training process of its members. In its journey, the party did not fully become a cadre party because it needed the support of voters from all people. This reconstruction of the party uses historical methods consisting of heuristics, criticism, interpretation, and historiography. The results of this article illustrate that the development of the Prosperous Justice Party in Jepara was initiated in 1999 under the name Justice Party. In 2003, this party became the Prosperous Justice Party which in 2004, this party in Jepara became one of the participants in the election by getting a seat in the election. In the 2009 elections, the party won two seats in parliament, although the number of votes decreased compared to the previous election. The Prosperous Justice Party is not only involved in politics but also in the economic, social and health sectors